PENGARUH PERMAINAN TURN OVER TERHADAP PENGETAHUAN MENCUCI TANGAN PADA ANAK USIA 2-3 TAHUN DI KB BINTANG CENDEKIA KECAMATAN TAMPAN KOTA PEKANBARU - Ayu Oktafia; Daviq Chairilsyah; Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on the results of field observations on the ability to hand washing knowledge of students has not developed optimally. So it is necessary to apply the turn over game. The purpose of this study was to examine the effect of using turn over game on the ability to hand washing knowledge of children age 2-3 years. This research was conducted at KB Bintang Cendekia Tampan District Pekanbaru City, during January 2019 to Apr 2019 for observation and research. The research used experimental method with one group pre-test post-test design with 12 samples. The data collection technique used in this research is using observation sheet the ability to hand washing knowledge of student. Data anlisis technique using t-test by using SPSS program ver 20. From result of data analysis obtained tcount equal to 19,768 bigger than t table = 2,201 with sig 0.000 <0.05. It can be concluded that there are differences in the ability to hand washing knowledge significantly before and after the application of the turn over game. Based on hypothesis test results obtained there is the effect of use turn over game to the ability to hand washing knowledge of children age 2-3 years KB Bintang Cendekia Tampan District Pekanbaru City of 61,64% .Key Words: Turn Over, Hand Washing Knowledge